CELEBRATING DIVERSITY: A HOLISTIC APPROACH TO HEALTH EQUITY IN HOMOAFFECTIVE RELATIONSHIPS - Silva, Ricardo Jorge; Santos, Ana Carolina (Research Journal of Health, Medicine and Nursing, 2024)
The Portuguese Constitution enforces the principle of equality, proclaiming that all citizens share the same social dignity and are equal before the law. This commitment to equality is emphasized in Article 64, which grants everyone the right to health protection and the duty to advocate for its promotion. It is indisputable that good sexual health is an essential facet of overall well-being. Membership in a sexual minority should never serve as a barrier to accessing healthcare services. Historically, discussions around sexuality have been shrouded in myths and taboos, often accompanied by discrimination, stigma, and social exclusion. These societal attitudes can significantly impact health outcomes. Sexuality is multifaceted, encompassing dimensions like sexual orientation, identity, gender roles, sexual practices, and various biological, psychological, psycho-emotional, and cultural aspects. Human sexuality serves as a driving force that motivates individuals to seek love, connection, tenderness, and intimacy. Throughout the cultural and biological evolution of humanity, the approach to sexuality has evolved, intertwining with feelings, actions, interactions, and influencing both physical and mental health. Sexual orientation, sexual behavior, and sexual fantasies are distinct elements within the broader realm of sexuality, with each playing a unique role in individual lives. Recognizing the importance of sexuality in human existence, we must navigate its complexities while respecting cultural, moral, and ideological values to ensure that it enhances rather than impedes the quality of life.